Development of an In Vitro Methodology to Assess the Bioequivalence of Orally Disintegrating Tablets Taken without Water - Toshihide Takagi; Takato Masada; Keiko Minami; Makoto Kataoka; Shinji Yamashita (MDPI AG, 2023)
To assess the probability of bioequivalence (BE) between orally disintegrating tablets (ODTs) taken without water and conventional tablets (CTs) taken with water, an in vitro biorelevant methodology was developed using the BE Checker, which reproduces fluid shifts in the gastrointestinal tract and drug permeation. In addition to the fluid shift from the stomach to the small intestine, the process of ODT disintegration in a small amount of fluid in the oral cavity and the difference in gastric emptying caused by differences in water intake were incorporated into the evaluation protocol. Assuming a longer time to maximum plasma concentration after oral administration of ODTs taken without water than for CTs taken with water due to a delay in gastric emptying, the fluid shift in the donor chamber of the BE Checker without water was set longer than that taken with water. In the case of naftopidil ODTs and CTs, the values of the f2 function, representing the similarity of the permeation profiles, were 50 or higher when the fluid shift in ODTs taken without water was set at 1.5 or 2 times longer than that of the CTs taken with water. The values of the f2 function in permeation profiles of pitavastatin and memantine ODTs were both 62 when the optimized experimental settings for naftopidil formulations were applied. This methodology can be useful in formulation studies for estimating the BE probability between ODTs and CTs.